Peran Emosi dalam Komunikasi Antarbudaya : Study Etnografi pada Komunitas Multikultur - Almadina Rakhmaniar (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
This research explores the role of emotions in intercultural communication through an ethnographic study of a multicultural community. Findings show significant variations in patterns of emotional expression across different ethnic groups and cultures, where cultural norms play an important role. Emotions such as joy, anger and disappointment are expressed differently based on cultural background, with examples such as East Asian holistic approaches compared to North American individual focus. Emotion regulation strategies also vary, influenced by the situation, individual disposition and cultural adaptations. Cultural values, norms and beliefs impact emotional experiences, with the interaction of gender and culture shaping the perception and expression of emotions. Emotions play a key role in the dynamics of intercultural interactions, influencing relationship formation and the potential for conflict. Practical implications emphasize the importance of culturally sensitive communication for effective diversity management in organizations, improving team efficiency, and supporting organizational change. The research contributes theoretically by offering insights into the complexity of emotional processes in culturally diverse environments, enriching intercultural communication theory and the psychology of emotion. These results confirm the importance of an in-depth understanding of cultural diversity in emotions to promote more harmonious and effective interactions in multicultural environments.